THE INFLUENCE OF PROFESSIONAL COMPETENCE AND TEACHER CREATIVITY ON THE PERFORMANCE OF ELEMENTARY SCHOOL TEACHERS IN KLAKAH DISTRICT - Selvi Nur Lailiyah; Singgih Bektiarso; Ridho Alfarisi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to determine the influence of professional competence and teacher creativity on the performance of elementary school teachers in Klakah District. The design used is descriptive correlational. The sample contains 150 teachers selected through proportional random sampling technique. Data was collected through questionnaires and analyzed using multiple linear regression after fulfilling the classical assumption test. The research results show that professional competence and teacher creativity together have a positive effect on teacher performance. The coefficient of determination (R2) value of 0.413 indicates that professional competence and teacher creativity together explain 41.3% of the variation in teacher performance. These results reinforce the crucial importance of developing professional competence and teacher creativity in efforts to improve the quality of educator performance in elementary schools.